Physicochemical analysis on tempeh samples available at Kuala Lumpur supermarket and sensory evaluation of tempeh patty - Law, Chai Jia; Nur Syamimi Farahin Fazil,; Mohd Noor Hidayat Adenan,; Hasnah Haron, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aimed to determine the physicochemical properties of fresh tempeh samples available in Kuala Lumpur supermarkets. The proximate composition, mineral content, and color of the fresh tempeh were assessed. One of the fresh tempeh samples was selected to create three formulations of tempeh patty, which were then subjected to sensory analysis. Seven attributes of the tempeh patty-aroma, color, appearance, texture, taste, nutty taste, and overall acceptance were evaluated by 40 panelists. The average macronutrient content of tempeh in Kuala Lumpur supermarkets was 61.47 ± 0.43% moisture, 0.84 ± 0.02% total ash, 20.10 ± 1.3% crude protein, 0.66 ± 0.30% crude fat, and 16.89 ± 1.47% total carbohydrate. The average mineral content per 100 g of tempeh was 0.11 ± 0.03 mg Fe, 3.29 ± 1.08 mg Zn, 2.38 ± 0.68 mg Na, 304.62 ± 35.98 mg Mg, and 466.40 ± 220.48 mg Ca. Color analysis revealed an average brightness (L*) of 73.8 ± 0.27, redness (a*) of 3.42 ± 0.02, and yellowness (b*) of 17.02 ± 0.07. The study found significant differences (p<0.05) in moisture, total ash, Mg, and color (L*, a*, b*) among the raw tempeh samples. Significant differences (p<0.05) were observed only in the aroma and color attributes for the three tempeh patty formulations. In conclusion, significant differences were identified in the moisture, ash, crude protein, carbohydrate, and magnesium content among the tempeh samples collected from Kuala Lumpur supermarkets. The nutrient content data obtained from this study can serve as a reference for various stakeholders, and the tempeh patty has the potential to be developed as a healthy tempeh-based dish.